151k views
0 votes
7xy - x2t + 4xy + 5xt

2 Answers

0 votes

Answer:

x(11y + 3t)

Explanation:

7xy - x2t + 4xy + 5xt

x2t also can be written as 2xt

= 7xy + 4xy - 2xt + 5xt

= 11xy + 3xt

Take the common term out, we got:

x(11y + 3t)

Hope this helped :3

User Sasigarn
by
5.1k points
3 votes

Answer:

x[ 11y + t(5 - x)].

Explanation:

7xy - x^2t + 4xy + 5xt

= 7xy + 4xy + 5xt - x^2t

= 11xy + 5xt - x^2 t

= x(11y + 5t - xt)

= x[ 11y + t(5 - x)].

User Omar Alves
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.